Association between Sociodemographic Factors with Nutritional Status among Primary School Children in Setiu, Terengganu, Malaysia - Hussin, Napisah; Mamat, Nurul Liyana; Halib, Hasmiza; Yen, Wong Chee (Jurnal Gizi dan Pangan, 2024)
This study aims to determine the association between sociodemographic aspects and nutritional status among rural Setiu, Terengganu schoolchildren. A cross-sectional study using convenience sampling was conducted among 269 primary school children. Sociodemographic information was obtained from parents or guardians through face-to-face interviews, and standardized techniques and calibration were adopted for anthropometric measurements. The World Health Organization Anthro Plus was used to generate the z-scores for Weight-for-Age (WAZ), Height-for-Age (HAZ), and Body Mass Index-for- Age (BAZ) to indicate underweight, stunting, and obesity among the children. Chi-squared test was used to determine the association between sociodemographic factors and nutritional status. The children exhibited mean WAZ, HAZ, and BAZ scores of -0.66, -0.82, and -0.00, respectively. Approximately 13.8% of schoolchildren in this study were stunted, 16.7% were underweight, 8.9% were overweight, and 11.5% were obese. Age and the father's education level were significantly associated with WAZ (p=0.02 and p=0.001), household size was associated with HAZ (p=0.029), and BAZ was found to be associated with the father's income factor (p=0.03). This study discovered that the majority of results from the measurement of WAZ, HAZ and BAZ were in normal growth with 81 (79.4%), 230 (85.5%) and 196 (72.9%), respectively. In conclusion, this study indicates that most of the sociodemographic factors were not associated with nutritional status and the prevalence of malnutrition among primary school children in the rural areas of Setiu, Terengganu was lower than in the other rural areas.